VD_FINDINFO Décision / 2013 / 448 vom 30. Oktober 2012 - VD Tribunal cantonal (2012)
AVOCAT, HONORAIRES, DÉPENS, INDEMNITÉEN GÉNÉRAL, JUGE UNIQUE | 429 al. 1 let. a CPP (CH), 429 CPP (CH), 14 al. 3 LVCPP